2014
DOI: 10.11604/pamj.2014.17.78.3464
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with interruption of treatment among pulmonary tuberculosis patients in Plateau State, Nigeria, 2011

Abstract: IntroductionNigeria has one of the highest tuberculosis (TB) burdens in the world with estimated incidence of 133 per 100,000 populations. Multi-drug resistant TB (MDR-TB) is an emerging threat of the TB control in Nigeria caused mainly by incomplete treatment. This study explored factors that affect adherence to treatment among patients undergoing direct observation of TB treatment in Plateau state, Nigeria.MethodsBetween June and July 2011, we reviewed medical records and interviewed randomly selected pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 9 publications
(5 reference statements)
3
65
1
11
Order By: Relevance
“…This finding is contrary to some studies conducted in northern Nigeria. 13,14 However, studies have shown that poor knowledge of TB could contribute to high burden of TB due to patients' poor health seeking behavior such as looking for inappropriate care. 15,16 Although many patients understand the need to seek care in approved health institutions, it has been shown that they do not fully assimilate the information they are receiving from the health care providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is contrary to some studies conducted in northern Nigeria. 13,14 However, studies have shown that poor knowledge of TB could contribute to high burden of TB due to patients' poor health seeking behavior such as looking for inappropriate care. 15,16 Although many patients understand the need to seek care in approved health institutions, it has been shown that they do not fully assimilate the information they are receiving from the health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Consistently, inadequate knowledge of TB treatment especially treatment duration has been associated with treatment interruption. 13 Suboptimal patients' compliance is a practical implication of poor TB knowledge. In real terms, when patients observe improvement in their health arising from the effective use of TB-medications within few weeks of treatment at the DOT centres, they stop taking medication.…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly one major reason why TB control in the country has remained ineffective. 4,13,14 The relative lack of professional preparation in DOTS management of TB was probably an important factor why virtually all the participants (97.3%) considered the proposed training necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Patients, who show no clinical improvement following treatment, harbor multi-drug resistant strains which are capable of posing a threat to their immediate environment [19].…”
Section: Discussionmentioning
confidence: 99%